Threats across boundaries: the spread of ESBL-positive Enterobacteriaceae bacteria and its challenge to the “one health” concept - Zhang, Shaqiu; Yang, Jing; Abbas, Muhammad; Yang, Qian; Li, Qianlong; Liu, Mafeng; Zhu, Dekang; Wang, Mingshu; Tian, Bin; Cheng, Anchun (Frontiers in Microbiology, 2025)
β-lactam antibiotics are essential medications for treating human diseases. The spread of extended-spectrum β-lactamase-producing Enterobacteriaceae (ESBL-PE) exists globally in multiple reservoirs and the natural environment and poses an immense threat to public health. Plasmid incompatibility groups, such as IncFIA, IncI1, IncY, IncFIB, IncN, IncFIC, IncX4, IncB/O/K/Z, IncHI1/2, and IncA/C, which exist in humans, animals, and the environment, carrying blaCTX-M, blaTEM, and blaSHV genes. The ISEcp1 upstream and orf477 downstream of blaCTX-M genes, as well as other mobile genetic elements (MGEs) such as IS903 and IS26, are involved in capturing and mobilizing antibiotic-resistant genes (ARGs). The blaCTX-M-15 gene is the most common among all discussed reservoirs. The environmental reservoir and propagation mode of ESBL-PE are increasing and difficult to control. The reasons include but are not limited to bacterial adaptability and horizontal gene transfer (HGT) mediated by MGEs and plasmids. Conjugation is a pathway of HGT that is almost uncontrollable. MGEs and plasmids such as Tn3, IS1380 families, IncI1, IncK, and IncN are facilitating HGT of blaCTX-M genes. This review highlights the need to monitor trends in antimicrobial resistance (AMR) in the natural environment. Therefore, policies such as antibiotic management plans, training for healthcare providers and/or patients, cautious use of antibiotics, the need for epidemiological networks, pre-travel consultations, World Health Organization (WHO) infection control and biosafety guidelines, and other intervention measures are considered desirable.